Histopathological & Lymphoproliferative effects for some experimental nanovaccines prepared from some bacteria - Layth Ibrahim Oleiwi AL-Shibbani; Ziad M. F. Alkhozai (Al-Qadisiyah Journal of Pure Science, 2017)
Chitosan used as carrier nanoparticles (CNP), where used at low-molecular-weight chitosan (LWCS) and loading antigens on Chitosan nanoparticles. After LD50 of LPS antigen were determined (239 Î¼g/ml of LPS of Salmonella typhi, 183 Î¼g/ml of LPS of Vibrio cholerae and 160.5 Î¼g/ml of LPS of Brucellae melitensis), and mixed these LPS to prepare Triple LPS antigen. The experimental study included 45 Albino Swiss male rats which divided into nine groups, 5 rats in each group. The results showed occurring pathological and inflammatory changes in spleen and thymus gland in rats vaccinated with LPS alone such as depletion of white pulp, proliferation of red pulp and sever congestion with hemosidrosis, while in case of rats vaccinated with LPS and chitosan showed occurring immunological and inflammatory changes such as proliferation of white pulp and normal red pulp, and increment in the size and numbers of the lymph node, also increment in the size of the germinal centers.